الدين كمصدر للمعنى - جابر,فاطمة (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة لإثبات ان الدين يعتبر مصدرا لإضفاء المعنى حسب رأي العالم مرسيا الياد، ويتبين ذلك من خلال فصول الموضوع، حيث يقدم الفصل التمهيدي الخلفية النظرية لفهم كيفية مساهمة الدين في إضفاء المعنى على حياة الأفراد، يناقش فيه المفاهيم التي تشرح دور الدين في تزويد الأفراد بنظام قيمي وأخلاقي وإجابات على الأسئلة الوجودية. حيث يستعرض الفصل الأول تحليل مرسيا الياد عالم الأنثربولوجيا حول دور الدين في تشكيل المعنى، ويركز الياد على المفاهيم الدينية مثل "المقدس والتكرار" ودورها في تنظيم حياة الأفراد والمجتمعات، يعتبر الياد ان الدين يخلق جسرا بين الانسان والعالم الميتافيزيقي مما يمنح الحياة اليومية بعدا أعمق ومعنى يتجاوز الحياة المادية. يناقش الفصل الأخير كيف يساهم الدين في مواجهة الفوضى واللامعنى التي قد تسيطر على حياة الأفراد والمجتمعات خاصة في الأوقات الصعبة والأزمات يساعد الدين الأفراد بالتمسك بقيمهم ومعتقداتهم حتى يتغلبو على مشاعر الضياع والفراغ، كما يوضح هذا الفصل كيف يمكن للمارسات والشعائر الدينية أن توفر الراحة النفسية وتساهم في بناء المجتمع متماسك ومترابط. This study aims to prove that religion is considered a source of meaning, according to the opinion of the scientist Marcia Eliad, and this is evident through the chapters of the topic. The introductory chapter provides the theoretical background for understanding how religion contributes to giving meaning to the lives of individuals. It discusses the concepts that explain the role of religion in providing individuals. With a value and moral system and answers to existential questions. The first chapter reviews the analysis of Marcia Eliad, an anthropologist, on the role of religion in shaping meaning. Eliad focuses on religious concepts such as “the sacred and repetition” and their role in organizing the lives of individuals and societies. Eliad believes that religion creates a bridge between man and the metaphysical world, which gives daily life a deeper dimension and meaning. It goes beyond physical life. The final chapter discusses how religion contributes to confronting the chaos and meaninglessness that may dominate the lives of individuals and societies, especially in difficult times and crises. Religion helps individuals adhere to their values and beliefs in order to overcome feelings of loss and emptiness. This chapter also explains how religious practices and rituals can provide psychological comfort and contribute to Building a cohesive and cohesive society.
عند مرسيا الياد
Keywords: ، التجربة الدينية; الطقوس; الشعائر; الأساطير; religion; sacred; meaning; religious experience; rituals; symbols; myths